The 3-Extra Connectivity of the Data Center Network BCube. (5th October 2021) - Yi, Yi; Fan, Jianxi; Cheng, Baolei; Wang, Yan; Yu, Jia
Abstract: Connectivity is a significant metric to assess the fault tolerance of a network. For a faulty vertex set H, the h -extra connectivity is defined under the assumption that every component of the network removing H has at least h+1 fault-free vertices. Compared to the traditional connectivity, which is defined under the assumption that the network removing H is disconnected or trivial, the h -extra connectivity can better reflect the true fault tolerance of the network. The BCube is an important server-centric data center network; it has good fault tolerance and scalability. In this paper, our research focuses on the logical structure of BCube, named BC_n, k, which is actually a specific type of generalized hypercubes. We prove that the 3-extra connectivity of BC_n, k is 4(k+1)(n-1)-4n for k≥ 4 and n≥ 4 .